Length of hospital stay in aneurysmal subarachnoid hemorrhage patients without vasospasm on angiography: potential for a fast-track discharge cohort. (2nd June 2021) - Catapano, Joshua S; Srinivasan, Visish M; Rumalla, Kavelin; Labib, Mohamed A; Nguyen, Candice L; Cole, Tyler S; Baranoski, Jacob F; Rutledge, Caleb; Rahmani, Redi; Lawton, Michael T; Ducruet, Andrew F; Albuquerque, Felipe C
Abstract : Background: Patients with aneurysmal subarachnoid hemorrhage (aSAH) frequently suffer from vasospasm. We analyzed the association between absence of early angiographic vasospasm and early discharge. Methods: All aSAH patients treated from August 1, 2007, to July 31, 2019, at a single tertiary center were reviewed. Patients undergoing diagnostic digital subtraction angiography (DSA) on post-aSAH days 5 to 7 were analyzed; cohorts with and without angiographic vasospasm (angiographic reports by attending neurovascular surgeons) were compared. Primary outcome was hospital length of stay; secondary outcomes were intensive care unit length of stay, 30 day return to the emergency department (ED), and poor neurologic outcome, defined as a modified Rankin Scale (mRS) score >2. Results: A total of 298 patients underwent DSA on post-aSAH day 5, 6, or 7. Most patients (n=188, 63%) had angiographic vasospasm; 110 patients (37%) did not. Patients without vasospasm had a significantly lower mean length of hospital stay than vasospasm patients (18.0±7.1 days vs 22.4±8.6 days; p<0.001). The two cohorts did not differ significantly in the proportion of patients with mRS scores >2 at last follow-up or those returning to the ED before 30 days. After adjustment for Hunt and Hess scores, Fisher grade, admission Glasgow Coma Scale score, and age, logistic regression analysis showed that the absence of vasospasm on post-aSAH days 5–7 predicted discharge on or before hospital day 14 (OR 3.4, 95% CI 1.8 to 6.4, p<0.001). Conclusion: Lack of angiographic vasospasm 5 to 7 days after aSAH is associated with shorter hospitalization, with no increase in 30 day ED visits or poor neurologic outcome.